2008
DOI: 10.1007/s00217-008-0838-6
|View full text |Cite
|
Sign up to set email alerts
|

Breadmaking performance of protein enriched, gluten-free breads

Abstract: Soybean enriched rice based gluten free breads were designed incorporating a structuring agent (hydroxypropylmethylcellulose HPMC) and a processing aid (transglutaminase TG). At dough level the effect of increasing amounts of soybean protein isolate (SPI), HPMC and water was studied in the Mixolab. Mixing and thermal characteristics showed the significant effect induced by water, soybean protein isolate, HPMC and TG, allowing the selection of the appropriate amounts for the breadmaking performance of enriched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
150
4
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 241 publications
(199 citation statements)
references
References 42 publications
28
150
4
9
Order By: Relevance
“…A strong correlation was found between width/height and SV (r=0.79 P<0.001). The specific volume values of the samples ranged from 1.5 to 2.3 ml/g, these results are in agreement with the ones reported for rice GFB (de la Hera et al 2013;Matos and Rosell 2012;Marco and Rosell 2008).…”
Section: Evaluation Of Bread Qualitysupporting
confidence: 91%
See 2 more Smart Citations
“…A strong correlation was found between width/height and SV (r=0.79 P<0.001). The specific volume values of the samples ranged from 1.5 to 2.3 ml/g, these results are in agreement with the ones reported for rice GFB (de la Hera et al 2013;Matos and Rosell 2012;Marco and Rosell 2008).…”
Section: Evaluation Of Bread Qualitysupporting
confidence: 91%
“…As the germination time increased, the springiness value decreased, indicating an increase in fragility and tendency to crumble when is sliced (McCarthy et al 2005). Indeed, after 12 h of germination springiness values were lower than the ones reported before in gluten free rice bread (Marco and Rosell 2008;Matos and Rosell 2012). These low values can be a limiting factor for the use of germinated brown rice for GFB.…”
Section: Evaluation Of Bread Qualitymentioning
confidence: 81%
See 1 more Smart Citation
“…Isolates and concentrates of these proteins are produced in high quantities, especially from soy and pea. Marco and Rosell (2008a) observed that the presence of legume proteins causes an increase in water absorption and modifies mechanical properties of the final product. In other studies an increase of specific volume and improvement of sensory quality were observed after an addition of pea protein, which was also accompanied by a decreased retrogradation (Miñarro et al 2012).…”
Section: Research Highlightsmentioning
confidence: 99%
“…This is an important factor to consider when gluten-free flours are to be used for gluten-free spaghetti for obtaining a viscous system that holds the food components cohesively in the matrix. Marco and Rosell (2008) reported that as a consequence of the initial starch gelatinization, dough consistency increased, improving the mechanical and handling properties of the rice flour dough compared with those of the dough mixed with water at 25°C. The pasting profile of the composite gluten-free flours reflected that the fabrication of gluten-free spaghetti containing up to 30% UPF was considered highly acceptable.…”
Section: Pasting Profilementioning
confidence: 99%